The Influence Of BTCLS Training On Emergency Knowledge Of Akkes Dharma Husada Kediri D III Nursing Program Students - Sucipto, Sucipto; Heny Kristanto; Puguh Santoso (Jurnal EduHealth, 2024)
Background: Basic Trauma Cardiac Life Support (BTCLS) is one of the knowledge and skills that a nurse must have. This training is an activity to improve skills, knowledge and skills for nurses in providing appropriate and fast services to patients.Research objective: To determine the effect of BTCLS training on emergency knowledge of students at the Dharma Husada Kediri Health Academy, Nursing Study Program. Method: Research design with a pre-experimental method with a one group pre-post test design approach. Population research is aimed at final year students. The research sample is 27 respondents consisting of 6th semester students. Research data collection uses questionnaires and data analysis uses t-test. Results: Research using a paired sample t-test of knowledge before and after training obtained a calculated value of 25.25 and a significance value of 0.000. Conclusion: There is an influence of BTCLS training on students' emergency knowledge. Suggestions for the need for BTCLS training to be carried out continuously to increase emergency knowledge competency.